Dari partisipasi ke polarisasi: dampak media sosial terhadap demokrasi di indonesia - Kurniawan, Dhafani Rizky (Maliki Interdisciplinary Journal, 2026)
Social media has emerged as a crucial element in the advancement of democracy in Indonesia as it promotes greater public involvement in political affairs. Platforms including Instagram, X, Facebook, TikTok, and YouTube offer opportunities for individuals to voice their views, stay informed about political matters, and observe government actions with increased transparency. Additionally, social media facilitates the rapid dissemination of political content, simplifying the process for individuals to obtain information and enhance their political consciousness. Furthermore, the youth utilize social media to engage in discussions regarding political topics, carry out social advocacy, and oversee electoral processes, thereby contributing to a more inclusive democratic framework. Nevertheless, social media also has detrimental effects, such as the propagation of false information, hate speech, political manipulation, and societal division, which can pose risks to the stability of democracy. Consequently, there is a need for digital literacy, ethical communication practices, oversight of misleading information, and educational initiatives on democracy to ensure the responsible usage of social media. By fostering collaboration among the community, governmental bodies, and digital platforms, social media can aid in building a healthy, transparent, and respectful democratic system in Indonesia.